Interrelation of the main hormonal markers in patients with metabolic syndrome - A. Prodan; O. Kamyshnyi; V. Dzhyvak (Kazimierz Wielki University, 2023)
Background. The study of the relationships between the main hormonal markers in patients with metabolic syndrome is relevant due to the growing prevalence of this syndrome in the world. The metabolic syndrome is a complex of risk factors, such as obesity, insulin resistance, hypertension and dyslipidaemia, and is known to significantly increase the risk of developing cardiovascular disease and diabetes. The aim. The aim is to trace the relationship between hormonal markers of metabolic syndrome and assess their impact on its development. Materials and methods. The study involved 96 participants from the Ukrainian population, comprising 53 cases of obesity and 43 non-obese individuals (controls), with no significant age and sex differences between the groups. The hormonal markers investigated included Leptin, Ghrelin, Adiponectin, and Resistin. The determination of serum levels was performed using specific ELISA kits, and correlation analyses were conducted to assess the associations between these markers. Results and discussion. The correlation analysis revealed a statistically significant close negative association between Ghrelin and Leptin levels (ρ = -0.633, p < 0.001). This implies that as Leptin levels decrease, Ghrelin levels tend to increase. The regression analysis demonstrated that 26.7% of the observed variance in Ghrelin levels could be explained by changes in Leptin levels. A strong negative correlation was observed between Adiponectin and Leptin levels (ρ = -0.818, p < 0.001). This indicates that as Leptin levels decrease, Adiponectin levels tend to increase. The regression analysis suggested that 54.8% of the observed variance in Adiponectin levels could be explained by changes in Leptin levels. The correlation analysis indicated a strong positive association between Resistin and Leptin levels (ρ = 0.776, p < 0.001). As Leptin levels increase, Resistin levels also tend to increase. The regression analysis suggested that 47.5% of the observed variance in Resistin levels could be explained by changes in Leptin levels. Conclusions. The study reveals significant correlations between hormonal markers in metabolic syndrome patients